If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -3 = 179 + -2y Reorder the terms: -3 + 8y = 179 + -2y Solving -3 + 8y = 179 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -3 + 8y + 2y = 179 + -2y + 2y Combine like terms: 8y + 2y = 10y -3 + 10y = 179 + -2y + 2y Combine like terms: -2y + 2y = 0 -3 + 10y = 179 + 0 -3 + 10y = 179 Add '3' to each side of the equation. -3 + 3 + 10y = 179 + 3 Combine like terms: -3 + 3 = 0 0 + 10y = 179 + 3 10y = 179 + 3 Combine like terms: 179 + 3 = 182 10y = 182 Divide each side by '10'. y = 18.2 Simplifying y = 18.2
| 2(x-4)-(6+x)=3x-4 | | ln(2-x)=0.5 | | =2(5g^2-14g+8) | | 7p+6=17 | | 4t+23=11t-2 | | 9=3/4(-12x+36) | | 6x+8y=4.1 | | 2k=7k+15 | | z+50=z+10+4z | | 3x-4(5x+7)=-130 | | 95+75x=96 | | u=(-(-2.42)±√(〖(-2.42)〗^2-4(1)(-102.64)))/(2(1)) | | y=8E-05x+0.0002 | | 99+v=5300/10 | | -20(20+-x)=100 | | -21-18=-3 | | 1/2(4x-16)=2(2x-8) | | -20(20+-x)=200 | | 5x+3y(2x)=22 | | 6m+2n+9m+8n= | | 21-18=-3 | | -20(20+-x)=800 | | x-4=40 | | 38s-10=0 | | 4y^2-6y+8y^2-5y= | | -20x+4=6+2x | | (x+2)(x-3)=2 | | 1/4x-2/3=y | | 3(k+3)=6(k-4) | | -15--4= | | -16x+5=6+5x | | 2x-1/x-7 |